Verification of Co-60 Source in Brachytherapy Equipment Using TW33005 Well-Type Chamber - Hemelia, Junita; Wardani, Pratiwi Sri; Intifadhah, Sahara Hamas; Zarkasi, Ahmad; Putri, Devina Rayzy Perwitasari Sutaji (Diponegoro University Semarang Indonesia, 2024)
Accidents in brachytherapy have occurred and are documented by the IAEA. These incidents are attributed to various factors, such as inaccurate sources, lack of independent verification, and equipment failures due to inadequate calibration. Verifying radioactive sources is crucial for ensuring patient safety. Verification is conducted to confirm that the measured source activity is accurate and stable. Accuracy and stability of source activity are two essential parameters in verification. Source activity accuracy indicates how closely the measured source activity aligns with the reference source activity, while source activity stability reflects the well-type chamber's ability to produce consistent results over time. This study aimed to verify the Co-60 sources at Dr. Kanujoso Djatiwibowo General Hospital using a TW33005 well-type chamber and analyze the results against national and international standards. The results showed that the Co-60 source activity values remained accurate and stable over five months. The highest accuracy was observed in November 2023 (-2.011%), while the lowest was in October 2023 (-2.397%). The highest stability was recorded in September 2023 (-0.416%), and the lowest in October 2023 (-2.090%). In conclusion, the Co-60 sources at Dr. Kanujoso Djatiwibowo General Hospital met the accuracy standards set by ESTRO and BAPETEN of 3% to 5% and the stability standard set by the IAEA of ±3%. This indicates that the sources are safe for use in brachytherapy.